Acetylsalicylic acid as the only pharmacological method for the prevention of preeclampsia: A retrospective study - Olga M. Kravtsova; Pavel A. Kuznetsov; Lela S. Dzhokhadze; Yulia E. Dobrokhotova; Aleksandr M. Zatevalov (IP Berlin A.V., 2023)
Background. Preeclampsia (PE) complicates 28% of pregnancies worldwide, negatively impacting the pregnant woman and the fetus. Therefore, its prevention remains relevant. It is believed that the cause of PE, especially early PE, is a placentation disorder. It warrants studying drugs that can improve placenta development. The leadership in this matter is maintained by acetylsalicylic acid, which, according to the ASPRE study, reduced the incidence of PE at 34 weeks of pregnancy by 82%. The use of low molecular weight heparins (LMWH), dipyridamole, and antioxidants for PE prevention remains controversial and continues to be studied by foreign and Russian scientists. Aim. To assess the efficacy of acetylsalicylic acid, LMWH, dipyridamole (Curantyl), and bovine blood derivates (Actovegin) in the Russian population of pregnant women at high risk for PE prevention. Materials and methods. The study included 244 patients. We reviewed the archived case records of 103 patients diagnosed with severe PE, who delivered in 2019 at the State Clinical Hospital №24, and 141 pregnant women from the Maternity clinic №3 at the Veresaev Moscow State Clinical Hospital, where the risk of PE was assessed as high, according to the results of extended combined screening of the first trimester of pregnancy. Eighty-nine pregnant women received acetylsalicylic acid at a dose of 75 mg and 54 at a dose of 150 mg. In addition, 22 patients received LMWH, 6 dipyridamole, and 3 Actovegin. The absolute risks, the risk ratio, and statistical significance when taking drugs in each risk group were calculated to assess the efficacy of acetylsalicylic acid and other drugs for PE prevention in the above risk groups. Results. The resulting weak inverse correlation (r=-0.31) between the PE severity at delivery and the dose of acetylsalicylic acid indicates that an increase in the acetylsalicylic acid dose was associated with a decrease in the PE severity. The effectiveness of combinations of various drugs for PE prevention was assessed by analyzing factor correspondences. Two-dimensional scaling of the most likely combinations showed that most patients received acetylsalicylic acid in the high-risk group with no PE. Additional use of LMWH, Curantyl, and Actovegin did not reduce the risk of PE. Conclusion. Acetylsalicylic acid is the only pharmaceutical method for preventing PE in high-risk groups. Higher doses of acetylsalicylic acid are associated with lower PE severity.